Optimum subdivision of curved hull plates for efficient ship manufacture using minimum strain energy - Kim, Jung (2013)
In this article, a novel hull subdivision method is presented. Hull subdivision is a process to subdivide the hull shape into smaller pieces, each of which can be fabricated individually. It is an important step since the fabrication time and cost depend on how the hull shape is subdivided. This process, however, has been done heuristically using experienced workers’ know-how, which makes it difficult for automation due to the difficulty of quantifying the workers’ expertise in an objective manner. Furthermore, the performance evaluation of the subdivision work has not been conducted. In this work, the subdivision process has been analysed using mechanical and mathematical theories considering strain energy and welding length of a plate, and a systematic procedure to perform subdivision using the differential evolution method, a combinatorial optimisation scheme, is proposed. The proposed method is tested with examples obtained from an existing ship, which demonstrates that the proposed method has the potential for replacing the current manual subdivision process.